Conversion of Jatropha Curcas Oil to Biodiesel in One-Step Transesterification Using Cowbone Derived CaO/Al2O3 with Fe2(SO4)3 Catalyst - Nelson Evangnum Jack ,; Suleiman Yunusa,; Abdulkareem Abubakar,; Haruna Ibrahim, (Journal of Science and Technology, 2025)
Mixture of Ferric sulphate (Fe2(SO4)3) and Calcium oxide (CaO) supported with alumina were employed as catalysts in this study. Production of biodiesel from edible sources is a threat to food security globally, to alleviate this problem biodiesel can be produced through the exploration of non-edible oils as raw materials and the use of waste resources. This work contributes to the development of a catalyst from waste cow bone supported with alumina for single step transesterication of jatropha curcas oil. The optmal conditions were observed at catalyst loading of  5 wt %,  methanol to oil mole ratio of 15:1, reaction temperature of 60 oC and reaction time of 2 hours. Fe2(SO4)3 to CaO/Al2O3 ratio of 4:1 gave optimum conversion as indicated by Gas chromatography-mass spectrometry (GCMS) of fatty acid methyl ester (FAME) of 96.72% using cowbone derived  CaO and 97.01% using the commercial CaO at optimum conditions. Fourier Transformed Infrared Spectroscopy (FT-IR) analysis showed important peaks in 1750 – 1730 cm-1 that confirm the presence of biodiesel. From the fuel characteristics of jatropha curcas oil methyl esters were found to be well within the range recommended by ASTM D6751 for biodiesel. Therefore, the waste-bone catalysts produced for transesterification of jatropha curcas oil successfully produced biodiesel from jatropha curcas oil using one-step simultaneous esterification and transesterification with ferric sulphate to CaO/Al2O3. The study's results suggest that non-edible jatropha curcas oil could be a good substitute for petro-diesel. Brunauer?Emmett?Teller (BET) surface area of CaO/Al2O3 was found to be 533.9 m2/g with pore volume of 0.2722 cc/g and width of 2.647nm while that of CaO was found to be 427. 5 m2/g.